Coating of Pd/C catalysts with Lewis-acidic ionic liquids and liquid coordination complexes – SCILL induced activity enhancement in arene hydrogenation. Issue 44 (23rd May 2017) - Lijewski, Martin; Hogg, James M.; Swadźba-Kwaśny, Małgorzata; Wasserscheid, Peter; Haumann, Marco
Abstract : Acid doping – coating of Pd/C catalysts with Lewis-acidic liquid films results in increased hydrogenation activity at very mild reaction conditions. Abstract : New solid catalysts with ionic liquid layer (SCILLs) were prepared by the coating of heterogeneous Pd/C catalysts with a thin film of acidic liquid: a known chloroaluminate ionic liquid (IL), [BMIM]Cl/AlCl3, and a recently developed liquid coordination complex (LCC), urea/AlCl3 . Both coatings improved the activity of Pd/C catalyst against toluene hydrogenation; at lower temperatures (40 °C) the IL-SCILL performed better, whereas at 80 °C the LCC-SCILL gave higher conversion. A thin film of ionic liquid proved to be sufficient to increase activity, while larger volumes of ionic liquid resulted in a decrease in activity due to pore blocking and hence mass transport limitations. Kinetic investigations in batch mode revealed a zero order with respect to toluene concentration, a first order in hydrogen pressure, and activation energy of 64.7 kJ mol −1 for the Pd/C catalyst. The SCILL catalysts had slightly lower values of 53.1 kJ mol −1 for [BMIM]Cl/AlCl3 and 61.4 kJ mol −1 for urea/AlCl3, respectively.